Propuesta de planeación estratégica para la Empresa Transportes Sol De Colombia S.A.S (2022)
Currently, in Colombia there is a high rate of creation of new companies, a practice linked to entrepreneurship, it can be affirmed that the high rate of unemployment is one of the main factors causing the high rate of company creation in Colombia. Just as new companies are created at an impressive speed, a high rate of closure or bankruptcy of these has also been identified, of all the companies registered in the chambers of commerce per year, more than 80% do not exceed the first three years of operation. When investigating in the literature the probable cause for which such a high percentage of registered companies fail in such a short time, it was possible to determine that in many cases the founders, managers and/or administrators of these new ventures did not carry out strategic planning or carried it out incorrectly, confusing it with other types of planning